Middle East link of terrorist threats from the perspective of pesantren in Indonesia: case study in the area of Malang - Yumitro, Gonda; Abdel Salam, El Fatih Abdullahi; Mohamad Shukri, Syaza Farhana (2020)
Purpose of the study: This article elaborates on the perspective of pesantren towards the Middle East link of the terrorist threat in Indonesia and their notion on the policies conducted by the Indonesian government, especially in the area of Malang. Methodology: This research is qualitative research by in-depth interviews, literature reviews, and focus group discussion (FGD) collecting data methods. The objects of this research were several pesantren leaders from different backgrounds such as Al Irsyad, Hidayatullah, Muhammadiyah, the Muslim Brotherhood, Nahdatul Ulama (NU), and Salafi. The data were analyzed using Nvivo 12 Plus and discussed with various literature reviews to perform the finding. Main Findings: The pesantren considers that increasing cooperation between state agencies and groups that are judged as having a link to sources for radical ideology in the Middle East would help minimize the problem of radicalism and the threat of terrorism in Indonesia, especially in the Malang area. Therefore, in assessing and deciding various policies on Islamic terrorism, the government needs to consider the Islamic discourse as not to be misled by public opinion. Applications of this study: This study is helpful for the government to evaluate its policies to face the issues of terrorism by understanding the Middle East link of terrorism in Indonesia based on the perspective of pesantren. Moreover, in a terrorism study, this article can be a reference source to analyze the issues. Novelty/Originality of this study: The growing terrorism in Indonesia is often associated with pesantren as these institutions are assumed to have the potency of supporting radicalism. Moreover, they have an ideological and network connection with the Islamic movements in the Middle East. On the other hand, pesantren is claimed to be a means of spreading peaceful Islam and is ready to cooperate with the government in handling the issue of terrorism in Indonesia.